A comparative assessment of salt marsh crabs (Decapoda: Brachyura) across the National Estuarine Research Reserves in New England, USA. Issue 1 (16th November 2019) - Raposa, Kenneth B; Goldstein, Jason S; Grimes, Kristin Wilson; Mora, Jordan; Stacey, Paul E; Mckinney, Richard A
Abstract: Salt marsh degradation and loss is accelerating in many regions of the United States as well as worldwide. Multiple stressors are often responsible, sometimes including crab burrowing and herbivory. A recent national assessment identified stark differences in crab indicators between northern and southern New England, with the latter exhibiting intense signs of impacts by crabs, but more details on crab patterns across the entire region are needed beyond this "broad-brush" assessment. Our study used green crab ( Carcinus maenas (Linnaeus, 1758 )) traps, intensive marsh platform burrow counts, and a new multi-metric index of relative crab abundance to examine patterns in marsh crabs across four National Estuarine Research Reserves in New England. Crab indicators from the multi-metric index and burrow counts were higher in southern New England marshes; patterns from trapping of green crabs were less clear. At the marshes examined, green crabs were very abundant in Maine, lower in New Hampshire, and intermediate in southern New England. Our study confirms that abundance and impacts by crabs vary dramatically between sites in northern and southern New England, and provides improved context for managers and researchers when considering impacts to marshes from multiple crab species across New England and elsewhere.